Internalisasi Nilai Ke-NU-an di SMK Andalusia Wonosobo: Study Manajemen Kemitraan - Nurhidayah, Atikah; Muntaqo, Lutfan; Syam, Robingun Suyud El (STAI Denpasar Bali, 2023)
This article reveals the internalization of NU values ​​at Andalusia Wonosobo Vocational School, using descriptive qualitative research and interactive analysis. The results of the research show that the internalization of NU values ​​at Andalusia Wonosobo Vocational School was carried out by establishing partners with Andalusian Islamic boarding schools, using the concepts of moderation (tawasuth), balance (tawazun), tolerance (tasamuh) and perpendicularity (i'tidal), which is done through three paths: understanding (knowledge), habituation, and example. This internalization is clearly visible through four indicators: national commitment, tolerance, anti-radicalism, and accommodating local culture. Research implications: the importance of partner involvement for the successful internalization of educational values. It is hoped that this study will contribute to the development of Islamic educational institutions.